Formação humana para o exercício da cidadania : os saberes da experiência de jovens membros do Conselho Municipal da Juventude de São Carlos - Fernandes, Sabrina (2008)
This study sought to understand, from the perspective of young people, the knowledge built on the experience of being members of the Municipal Council of Youth of São Carlos (CMJ). For both, departed from the consideration that our experiences can be as educational processes. That is, people also educate from the experiences that are over their lives. As we all have the experience of participation in the world, all have different knowledge, based on which we live until then. The survey was developed starting from the recognition of the existence of an oppressive system dominant in our society, what do we do this mainly through the imposition culture. In this context, education is understood as a possible way forward in seeking the release of such a system. The intervention in the world for this is always political act. Thus, politics is not restricted to our relationship with the state, because no human action is depoliticized, every human act is loaded with ideas about the society in which they live. And education is also impossible to remain neutral and can serve both the system of domination, as tool to be desarmá it. They are mainly in social practices that are outside trigger the imposition of education that can develop educational processes that build the possibility of an education that liberates. Based on these understandings, this study had to investigate an area of youth participation, the CMJ, now based on assumptions that were as educational. It is a legally defined area of intervention for young people in the direction of municipal public policies. From the development of a qualitative research, which took as a tool for collecting data reflect the conduct of interviews with four young holders of CMJ, emerged 6 categories through which the results are presented: 1. participation, 2. expanding the visions of the world, 3. all: being-a-with-the-other in the world, 4. tolerance and solidarity, 5. living and talking, 6. the knowledge of experience. Participation may be desencadeadora of numerous educational processes by enabling the interaction between various people. Well, from the interaction that it triggers in a participatory environment, people can come to develop a dialogue, expand their visions of world and understand themselves as belonging to all. In this way are likely to modify their actions facing the reality in which they live. Thus, participation may trigger educational processes to promote citizen training for a conscious action in reality, in the direction desired by the subject that participates.